2023
DOI: 10.1111/iju.15251
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective evaluation of the improvement in the urinary status‐related quality of life after robot‐assisted radical prostatectomy

Yuki Kohada,
Keisuke Hieda,
Shunsuke Miyamoto
et al.

Abstract: ObjectivesThis study aimed to investigate the characteristics of patients who report improvement in quality of life (QOL) related to urinary status after undergoing robot‐assisted radical prostatectomy (RARP) for localized prostate cancer.MethodsWe retrospectively reviewed the patients who underwent RARP between May 2010 and May 2021 at our institution and were preoperatively unsatisfied with their urinary status. Patients were grouped as Group 1 (improved patients: “satisfied” with urinary status based on int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Kohada et al used the International Prostate Symptom Score (IPSS)-QOL to identify a group of patients who were not satisfied with their urinary status (IPSS-QOL of 3-6 points) before robot-assisted RP (RARP) and examined the number of patients that improved to IPSS-QOL satisfaction (IPSS-QOL of 0-2 points) at 12 months after RARP. 3 The results revealed that IPSS-QOL improved to the satisfactory category in 72 of 237 patients (30.4%). Furthermore, multivariate analysis revealed the nerve-sparing procedure, low preoperative IPSS (total points of <11), and relatively better IPSS-QOL (3 points) compared with worse IPSS-QOL (4-6 points) as related factors.…”
Section: Editorial Commentmentioning
confidence: 90%
See 4 more Smart Citations
“…Kohada et al used the International Prostate Symptom Score (IPSS)-QOL to identify a group of patients who were not satisfied with their urinary status (IPSS-QOL of 3-6 points) before robot-assisted RP (RARP) and examined the number of patients that improved to IPSS-QOL satisfaction (IPSS-QOL of 0-2 points) at 12 months after RARP. 3 The results revealed that IPSS-QOL improved to the satisfactory category in 72 of 237 patients (30.4%). Furthermore, multivariate analysis revealed the nerve-sparing procedure, low preoperative IPSS (total points of <11), and relatively better IPSS-QOL (3 points) compared with worse IPSS-QOL (4-6 points) as related factors.…”
Section: Editorial Commentmentioning
confidence: 90%
“…Furthermore, multivariate analysis revealed the nerve-sparing procedure, low preoperative IPSS (total points of <11), and relatively better IPSS-QOL (3 points) compared with worse IPSS-QOL (4-6 points) as related factors. 3 These results indicate that patients with poor preoperative urinary QOL are unlikely to improve dramatically after RP. The nerve-sparing procedure help improve postoperative urinary QOL.…”
Section: Editorial Commentmentioning
confidence: 93%
See 3 more Smart Citations